IMPLEMENTATION MODEL OF MOTOR TRACTION FORCE OF MAGLEV TRAIN - Polyakov, V. O.; Khachapuridze, M. M. (Science and Transport Progress, 2016)
Purpose. Traction force implementation (TFI) by the motor of magnetic levitation train (MLT) occurs in the process of electric-to-kinetic energy transformation at interaction of inductor and armature magnetic fields. Ac-cordingly, the aim of this study is to obtain a correct description of such energy transformation. Methodology. At the present stage, a mathematical and, in particular, computer simulation is the main and most universal tool for analysis and synthesis of processes and systems. At the same time, radical advantages of this tool make the precision of selection of a particular research methodology even more important. It is especially important for such a large and complex system as MLT. Therefore the special attention in the work is given to the rationale for choosing the research paradigm selective features. Findings. The analysis results of existing TFI process model versions indicate that each of them has both advantages and disadvantages. Therefore, one of the main results of this study was the creation of a mathematical model for such process that would preserve the advantages of previous versions, but would be free from their disadvantages. The work provides rationale for application (for the purposes of research of train motor TFI) of the integrative holistic paradigm, which assimilates the advantages of the theory of electric circuit and magnetic field. Originality. The priority of creation of such paradigm and corresponding version of FI model constitute the originality of the research. Practical value. The main manifestation of practical value of this research in the opportunity, in case of use of its results, for significant increase in efficiency of MLT dynamic studies, on the condition that their generalized costs will not rise.